Charlie & the haunted tent - McKay, Hilary (London : Scholastic : [distributor] HarperCollins Distribution Services, 2008)
Charlie's big brother Max isn't scared of anything ... Except Aunt Emma's spooky house. At last it's Charlie's chance to be the hero. Those ghosts had better watch out.